Radical trade unionism in Britain, 1921-1991. - Communist Party of Great Britain; Communist Party of Great Britain. Archive Trust (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2021)
From its inception in 1920, the Communist Party of Great Britain (CPGB) was intimately involved in trade unionism in Britain. From entryism to election rigging, radical education of workers to support for legitimate industrial action, the CPGB took to trade unionism with particular zest and determination. This collection is comprised of material from the CPGB's Industrial Department, which sought to organise the party's strategy in relation to trade unions and industry.
Date range: 1921-1991.
Keywords: Communist Party of Great Britain. -- Industrial Department; Labor unions -- Great Britain